(untitled) (Piwulang: Jurnal Pendidikan Bahasa Jawa, 2025)
The degradation of local cultural values, particularly *unggah-ungguh* (Javanese etiquette), has become an urgent issue that needs to be addressed. One possible response is through engaging educational media that make learning *unggah-ungguh* easier for children to understand. This study aims to develop *Ayu lan Bagus* animation as a learning medium that incorporates the characters Ayu and Bagus to teach *unggah-ungguh* to elementary school students, while also preserving Javanese culture. The research method involves animation film development, including pre-production, production, and post-production stages. To enhance its effectiveness, the process is supported by the Design Thinking approach (Empathize, Define, Ideate, Prototype, and Test). The animation is designed using motion graphic techniques that are feasible for small teams and offer high sustainability. The *Ayu lan Bagus* episode on *unggah-ungguh* was tested at SDN Kebonagung, Imogiri, Bantul, involving 40 students from grades 1–2 and 5 teachers. Data were collected through observation, questionnaires, and documentation, and analyzed both quantitatively and qualitatively to measure the effectiveness and acceptance of the media. The results show that the *Ayu lan Bagus* animation successfully attracted students’ interest and received positive responses from the trial participants. Teachers also provided constructive feedback, stating that this medium is effective for Javanese language learning. The conclusion of this study indicates that the *Ayu lan Bagus* animation is feasible for further development as a fun and effective learning medium to instill local cultural values in the younger generation.